Analisis Jumlah UMKM Dan Jumlah Tenaga Kerja Terhadap Pertumbuhan Ekonomi Di Kota Langsa - Yusrizal Yusrizal; Nurjannah Nurjannah; Salman Salman (Pusat Riset dan Inovasi Nasional, 2023)
This study intends to discuss the effect of the number of micro, small and medium enterprises and the level of labor absorption on economic growth in Langsa city. as objectives among others to determine the effect of the number of MSMEs on economic growth in Langsa City, and to determine the effect of the level of employment on economic growth in Langsa City. This thesis uses quantitative data with the Multiple Linear Regression data collection method. Based on the research conducted, the following results and conclusions were obtained: the number of micro, small and medium enterprises and the amount of employment did not simultaneously affect economic growth in Langsa City.